PENGEMBANGAN KUALITAS PADEPOKAN SAROTAMA DITINJAU DARI ANALISIS SWOT - Prasetyo Adhi Tama; Nanang Yulianto (Surakarta: Jurusan Karawitan Institut Seni Indonesia Surakarta, 2022)
In terms of the intricacies of education in the arts, Padepokan Seni Sarotama cannot be separated from the figure of Mujiono. Mr. Mujiono's struggled as a karawitan teacher and Wayang puppeteer in 1985 when he opened the teaching of puppetry for children. Another motivation behind Mr. Mujiono's built art hermitage is the children who are not from the artist's family and do not yet have means of artistic expression so Padepokan Sarotama is present as a place of recreation and learning for students. The purpose of this research is to develop an organizational strategy at the Padepokan Sarotama. Furthermore, the method used in this research is the SWOT analysis, a strategic planning method used to evaluate Strengths, Weaknesses, Opportunities, and threats in a project or business. Based on that, analysis involves determining the objectives of the business venture or project and identifying internal and external factors, which is excellent and profitable to achieve that goal. Based on IE Matrix (Internal-External) analysis and SWOT quadrant, it can be concluded that the appropriate organizational strategy for Mr. Mujiono is as follows: Combination of generic strategy with a variety of strategies that include: 1) Horizontal integration, 2) Market penetration, and 3) Market development.